Generalized Solutions for Nonlocal Elliptic Equations and Systems with Nonlinear Singularities - Youtao Wang; Guangcun Lu (Abstract and Applied Analysis)
We use the topological degree method to study the existence of solutions for nonlocal elliptic equations (systems) with a strong singular nonlinearity.